Host suppression of quorum sensing during catheter-associated urinary tract infections - Stephanie J. Cole (Nature Portfolio, 2018)
Pseudomonas aeruginosa can cause chronic infections on medical devices by forming biofilms, a process regulated by quorum sensing (QS). Here, the authors show that P. aeruginosa is unable to perceive QS signals in the presence of either host urine or urea, and clinical isolates are often defective in QS.